Access to food retail outlets in County Durham, UK: a pragmatic cross-sectional study. (26th February 2015) - Mills, Susanna; Wright, Tim
Abstract: Background: Strong links exist between deprivation, obesity, and dietary quality. Increasing interest has focussed on the concept of access to food and so-called food deserts, defined by a policy working group of the UK Low Income Project Team in 1995 as "areas of relative exclusion where people experience physical and economic barriers to accessing healthy food". We aimed to establish the accessibility of food retail outlets in County Durham, a county in north-east England, UK, considering physical access, affordability, and food range and quality. Methods: In a pragmatic cross-sectional study in County Durham, we used information from town surveys and food business databases to locate and identify food retail outlets. The prevalence of deprivation, obesity, retail outlets, takeaway outlets, and ratio of retail to takeaway outlets was mapped, to establish local food access, and any associations with deprivation and obesity. The times taken to travel from residences to supermarkets using private car and public transport were also measured. 400 members of the community participated in eight focus groups and commissioned on-street surveys. Focus group transcripts were reviewed alongside the on-street survey responses to identify key issues. Findings: Most residents shopped at least weekly for food (n=368, 92%), used a supermarket for their main food shop (372, 93%), travelled for up to 15 min (340, 85%), and used a car for transport (188, 47%). Many survey respondents indicated high levels of satisfaction with food retail outlets (average rating 8·7 out of 10 for agreement with the statement "Overall I am satisfied with the shop where I do my main food shopping"), although financial constraints and transport inconvenience were identified as barriers. Difficulties with food shopping were more widely described in focus groups, and many individuals felt that local shopping provision had declined, with an emergent excess of takeaway outlets. Food retail access was reduced for the disabled, full-time workers, elderly people, and people with children. Interpretation: These findings suggest a potential role for individual behaviour change, planning and policy bodies, and the food retail industry in addressing food access. The multiple methods used in this study enabled triangulation; however, the conclusions are limited by the pragmatic nature of data collection and analysis. Funding: Durham County Council.